Pemberdayaan Masyarakat Dalam Pengolahan Sampah Organik Rumah Tangga Menggunakan Larva Black Soldier Fly (Hermetia Illuces) - Muhammad Bibin; Ani Ardian; Kaswiran Kaswiran (Jurnal Abdi Mandala, 2022)
Organic waste has always been the waste with the largest production in Indonesia. Therefore, technology is needed that is able to process organic waste and make it more useful. One of the efforts that is being implemented in Purwosari Village is to use Black soldier fly larva technology. Black soldier fly larvae have the ability to change organic waste so that it has use value. The objectives of this community service activity are (1) increasing the knowledge of the partner community regarding the use of the Black soldier fly fly, (2) providing knowledge to the partner community regarding the technology of processing household organic waste using Black soldier fly larvae, (3) increasing the knowledge and skills of the partner community about the use of Black soldier fly larvae as high protein fish feed, (4) increasing community knowledge in maintaining The black Warrior flies. The method used is the transfer of technology through lectures, training and mentoring. The result of this activity is that the partner community has learned the knowledge of processing household organic waste using Black soldier fly larvae. The skills of partner communities regarding the processing of household organic waste using Black soldier fly larvae are increasing and partner communities can provide alternative feed to their farmed fish. This activity has also attracted the interest of the community outside Purwosari Village, so that after the socialization session and discussion, many people came to the maggot cultivation site to learn firsthand how to get maggot seeds.